Healtime : Inovasi Digital untuk Analisis Penyakit melalui Platform Cerdas - M. Rifqi; A. Sjamsjiar Rachman (Universitas Mataram, 2024)
Health is an important aspect of life, especially in today's modern era. When health is compromised, a person's quality of life also decreases. Currently, public awareness of the importance of maintaining health is increasing, in line with the World Health Organization's view that health includes physical, mental, and social well-being, not just the absence of disease. Even so, many still underestimate the importance of prevention in maintaining health. Prevention is a very important initial step, because treating diseases that have developed is much more difficult and expensive. Technological advances, such as smartphones and the internet, make human life easier, but also reduce physical activity, triggering a sedentary lifestyle. This lifestyle can affect health in the long term, where many diseases arise due to unhealthy habits. Therefore, technology-based solutions, such as the Healtime platform, are relevant in helping to analyze health conditions quickly and encourage preventive measures to maintain health amidst lifestyle changes. Healtime also offers features to monitor daily habits, provide lifestyle recommendations, and support individuals in achieving a balance between work and personal health.